Development of E-Module Based Learning Media for A1 Level Reading Competency - Putri Nanda; Herlina Jasa Putri Harahap (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to develop E-module based learning media for A1 level reading literacy. This research was conducted in the library of the Faculty of Languages and Arts, Medan State University. In this research, creation research using Richey and Klein's theory is used. Among them are: (1) Planning stage, (2) Creation stage, (3) Evaluation stage. This research data consists of words, sentences and images on the topic